Under Construction Performing Critical Identity - Kohl, Marie-Anne (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
While currently identitarian ideologies and essentialist notions of identity that tend to simplify and reduce life experience to simple factors are globally regaining massive attention, it becomes inevitable to recollect the thorough discussions of identity concepts of the past three decades. It also calls for an ever keener awareness of and capacity to deal with the complexity and diversity of the world we live in. Artists play a major role in the potential reflection and transformation of perceptions and conceptions of the world - musicians, dancers, choreographers, spoken word artists, performance artists, actors, also fine art, installation, media artists or photographers alike. "Performing critical identity" points to performative practices of artists that bring to the fore a critical (self-)awareness and (self-)positioning concerning identification and belonging. Social identities such as gender, sexuality, race, class, dis/ability, age or non/religiosity are closely linked to the historical, social, regional and political dimensions of their formation. From this perspective, identities are hardly one-dimensional but complex and intersectional, and are rather to be thought of as a process of identification and belonging than as a consistent essence.As different, maybe contradictory among themselves, as they are, the performative works of artists such as Lerato Shadi, Liad Hussein Kantorowicz, Nora Chipaumire, Shu Lea Cheang, Zanele Muholi, Ohno Kazuo, Anohni Hegarty, Neo Hülcker, "We're Muslim. Don't Panic" or of theatre collectives such as RambaZamba and Thikwa Theater in Berlin or Theater Hora in Zurich, to name but a very small quite random selection of artists, share a critical approach towards hegemonic norms or stereotyping of identities and their representations, and empower diversity.This edition puts a specific focus on the performativity of the aesthetic practices, and wants to explore different artistic approaches, strategies, tactics and perspectives of artists when they address identity issues, when they target power relations and structures of oppression and inequality, when they empower concepts of diversity. This Call for Papers invites academic as well as artistic contributions that delve into case studies of artists performing critical identity or into more general theoretical reflections on the subject. Contributions can relate to, but are not limited to following topics: - intersectionality - subversion - (self-)empowerment - resistance - subalternity - exploitation - manipulation - (anti-)feminism - appropriation - cultural globalisation - transculturality - hybrid identities - collectives - body - stage - audience - de-/construction of the difference of aesthetic genres and of high/popular culture - capitalism - colonialism - (re-)production of exclusion